PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN BRI CORPORATE UNIVERSITY JAKARTA SELATAN - Susanti, Yulinda; Mawardi, Syamsi (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of the work environment and work motivation on the performance of BRI Corporate University South Jakarta employees. This research uses quantitative researchers. The population in this study were all employees of BRI Corporate University, South Jakarta, using Slovin sampling, which was obtained by 62 respondents. Data collection was done by means of a questionnaire. The data analysis method uses simple regression tests, multiple linear regression, correlation coefficient, coefficient of determination, partial t test and simultaneous F test. The results of this research show that: The work environment has a positive and significant effect on the performance of BRI Corporate University South Jakarta employees. This is proven from the simple linear regression equation Y = 18.722+0.561X1. The correlation value is 0.624 (strong). The coefficient of determination value is 38.9%. The t value is 6.181 > table 1.671 with a significance of 0.000 < 0.05. Work motivation has a positive and significant effect on the performance of BRI Corporate University South Jakarta employees. This is proven from the simple linear regression equation Y = 11.992+0.717X2. The correlation coefficient value is 0.738 (strong). The coefficient of determination value is 54.5%. The t value is 8.484 > t table 1.671 with a significance of 0.000 < 0.05. Simultaneously the work environment and work motivation have a positive and significant effect on the performance of BRI Corporate University South Jakarta employees. This is proven from the multiple linear regression equation Y = 11.835+0.037X1+0.684X2. The correlation coefficient value is 0.739 (strong). The coefficient of determination value is 54.6%. The Fcount value is 35.462 > Ftable 3.153 with a significance level of 0.000 < 0.05.